An Ultrafast Rechargeable Hybrid Sodium‐Based Dual‐Ion Capacitor Based on Hard Carbon Cathodes. Issue 18 (15th March 2018) - Chen, Suhua; Wang, Jue; Fan, Ling; Ma, Ruifang; Zhang, Erjing; Liu, Qian; Lu, Bingan
Abstract: Hybrid sodium‐based dual‐ion capacitors (NDICs), which integrate the advantages of supercapacitors and sodium‐ion batteries, have attracted tremendous attention recently. In this work, hybrid sodium‐based dual‐ion capacitors are successfully developed with nitrogen‐doped microporous hard carbon as the cathode and soft carbon as the anode. N‐doping is beneficial to the functional groups, porous structure, and electric conductivity of hard carbon. Hybrid NDICs possess a wide voltage range (0.01–4.7 V), high‐energy density of 245.7 W h kg −1 at a power density of 1626 W kg −1, long cycle life (1000 cycles), and outstanding rate performance. Abstract : Hybrid sodium‐based dual‐ion capacitors (NDICs) are successfully developed with nitrogen‐doped hard carbon as the cathode and soft carbon as the anode. Hybrid NDICs exhibit high capacity, excellent cycling ability, ultrahigh energy and power densities, and with fast charging and slow discharging performance (the hybrid NDICs can be fully charged in 40 s and discharged over more than 1200 s).